EFEKTIVITAS GAME ANDROID BAHASA INDONESIA (GABI )TERHADAP PENGUASAAN KALIMAT EFEKTIF PADA MAHASISWA UNIVERSITAS PEKALONGAN - Hanindya Restu Aulia; Afrinar Pramitasari (LPPM Universitas Pekalongan, 2017)
The aims of this study are to determine differences in mastery effective sentence studentswho are taught using GABI of students using conventional media and the effectiveness of GABI.This study used a quasi-experimental research methods pretest-posttest control group design.Determination of the sample using cluster random sampling (random sample based cluster) todetermine the class. Based on the results of the lottery accounting program as control class andnursery program as a experiment class. The validity of the instrument in the form of constructvalidity. Reliability of the instrument is calculated by reliability rating technique.The test resultsshowed that the prerequisite analysis and posttest-pretest scores were normally distributed andhomogeneous. Based on t-test analysis of data mastery effective sentence posttest control group andthe experimental group, obtained t count of 3.17, p equal to 0.002 (p <0.05). These results suggestthat there are significant differences between students using GABI and students who receivedlearning by conventional media in Unikal. Based on the results of t-test and an increase in the meanscores of control and experimental groups, obtained by t count 4.40, p equal to 0.000 (p <0.05), anincrease in the control group mean score of 0.81 while the experimental group mean score increasesby 4, 03. Based on the difference in mean score increase in the experimental group were higher thanthe control group, indicating that GABI more effective than power point as conventional media.